ANALISIS EARNING MANAGEMENT DAN RETURN PADA PERUSAHAAN MERGER DAN AKUISISI DI BEI TAHUN 2000-2010 - Komang Nia Gama Pertiwi; Nurul Hasanah Uswati Dewi (STIE Perbanas Surabaya, 2012)
It is demanded that any company should be able to compete so rigorously that they can survive in the global era. The way hot to do such an effort, among others, is by merging their firms or by acquisition. By doing so, the process will be much simple and the cost is also quite low. The purpose of this study was to analyze the practice of earnings management and return on corporate mergers and acquisitions that are listed on the Indonesia Stock Exchange period 2000-2010. There are two hypotheses, first hypothesis the researchers used independent sample t-test to see the difference of earnings management for the thirty firms as samples before the mergers and acquisitions and the companies whose incomes are increasingaccruals and those decreasing accruals. In the second hypothesis, the researchers used Wilcoxon signed ranks test to see the difference of stock returns for the 43 firm samples, one year before and after mergers and acquisitions. Based on the results of the first hypothesis, it was found there was a significant difference in accounting policies by the company in the practice of earnings management between income increasing accruals and income decreasing accruals of three years before mergers and acquisitions. While the results on the second hypothesis, it was found no significant difference of stock returns one year before and after mergers and acquisitions..